KERJASAMA INDONESIA - TAIWAN DALAM PENEMPATAN PEKERJA MIGRAN INDONESIA DI TAIWAN MELALUI SPECIAL PLACEMENT PROGRAM TO TAIWAN (SP2T) PERIODE TAHUN 2019 - 2022 - Ghea Ad Meliala, (2023)
This study aims to determine the cooperation between Indonesia and Taiwan in the field of employment in the placement of Indonesian migrant workers in the formal sector through the Special Placement Program to Taiwan (SP2T) and to determine the role of related parties in the implementation of SP2T by using the theory of international cooperation and the concept of international migration. The method used is descriptive qualitative using primary and secondary data sources. Data collection techniques were carried out by interviews and literature studies. The author uses four stages of data analysis according to Miles and Huberman, namely data collection, data reduction, data presentation, and drawing conclusions/data verification. The final results of this study indicate that the Indonesian government has actively collaborated with Taiwan in placing Indonesian migrant workers through SP2T to avoid exploitation of PMI and overcharging. The Indonesian migrant workers factor in formal sector of migrating to Taiwan is based on interest of salary considerations between the country of origin and the country of origin, the goal of limited job opportunities in the country of origin with a minimum of SMK graduates and access to society. An adequate number of high school graduates cannot be absorbed due to the decision of the selected candidate based on the authority of the employer company. It is proven that the reason why companies are unable to recruit many workers with the SP2T program is because the costs incurred by Indonesian migrant worker during the placement process are borne by the employer company. Keywords: Indonesia-Taiwan Cooperation, Placement of Indonesian Migrant Workers, Special Placement Program to Taiwan